The Role of Parents in Overcoming Juvenile Delinquency According to the Islamic Perspective - Bahy Rynar Murfid; Aceng Kosasih; Nurti Budiyanti (Universitas Muhammadiyah Malang, 2021)
Juvenile delinquency has become a common phenomenon in society. Although various efforts have been made in order to overcome this problem, the behavior of young people to show their existence in these deviant ways is never ending. Apart from creating a space for actualization to accommodate their various interests and talents, the role of parents is very important in dealing with juvenile delinquency. In particular, this article examines the role of parents in overcoming juvenile delinquency from an Islamic perspective. The purpose of this study is to find alternative solutions, especially solutions that come from family influences. Meanwhile, the method used in the research uses a research library, namely analyzing and reviewing various previous scientific articles. The results obtained from this study indicate that the role of parents is very important in overcoming juvenile delinquency. The presence of parents by inviting positive dialogue to their teenage children is needed so that they get exemplary figures from the attitudes and behavior of their parents. In this case, parents also need to teach their children with commendable morals (al-Akhlak al-Mahmudah).